Who should finance childcare? multilevel analysis of 24 countries - Dobrotic, I; Juros, TV (Pravni Fakultet Sveucilista u Zagrebu (Law School of the University of Zagreb), 2016)
This paper examines how the individual and country-level factors affect the childcare financing attitudes, particularly the effect of socialization in a particular welfare regime. This area of research is fraught with methodological and conceptual issues, including the over-reliance on Esping-Andersen’s regime typology. Therefore, the authors also investigate whether a more family- policy-nuanced categorization of welfare regimes better accounts for the cross-country variations in childcare attitudes. Using the 2012 ISSP data, the authors conducted the multilevel analysis of 24 European countries, and while the effect of most predictors is generally consistent with the previous research, this study’s most important finding is that the alternative Leitner’s "Varieties of Familialism" typology better accounts for the cross-national variations in childcare attitudes than the classical Esping-Anderson’s typology. This speaks of the importance of a programmatic approach in the welfare state attitudes analysis which links the public support for specific social programs to its unique characteristics.